Improving the Sound Absorption of Natural Waste Material-based Sound Absorbers Using Micro-perforated Plates. Issue 13 (1st December 2022) - Beheshti, Mohammad Hosein; Khavanin, Ali; Safari Varyani, Ali; Yahya, Musli Nizam Bin; Alami, Ali; Khajenasiri, Farahnaz; Talebitooti, Roohollah
ABSTRACT: Both natural and synthetic fibers do not perform well at low frequencies and are also subjected to erosion, moisture, fire, etc., when used as an interior finish of room walls. To overcome these problems, micro-perforated plate with different thickness is used in a multilayer sound absorber configuration to improve its sound absorption. Firstly, the acoustic properties of five natural wastes including sheep wool, goat wool, camel wool as well as pith and fiber bundles of sugarcane bagasse were determined by using an impedance tube following ISO 10534–2. Secondly, the effect of Panel thickness was investigated. The maximum sound absorption coefficient (SAC) of natural waste materials is at middle to high-frequency range and this shifted to lower frequency as the porous layer thickness increases. The sound absorption performance depends on the thickness of perforated plate and porous layer in a compound sound absorber. It is observed that the using perforated plate in the front of low thickness porous materials significantly improve the SAC and absorption bandwidth. However, it should be noted that this reduces the SAC at high frequencies. Accordingly, the thick micro-perforated panels backed by porous layer are not recommended to control sounds with frequency higher than 3000 Hz.